Milking of the Umbilical Cord in Term and Late Preterm Infants. (11th February 2019) - Basile, Stefano; Pinelli, Sara; Micelli, Elisabetta; Caretto, Marta; Benedetti Panici, Pierluigi
Abstract : Introduction . Umbilical cord milking is a procedure in which clamped or unclamped umbilical cord is grasped, and blood is pushed ("stripped") two to four times towards the newborn, in a rapid time frame, usually within 20 seconds. The target of umbilical cord milking is to provide infants with their whole potential blood volume—of which they are deprived when early cord clamping is carried out—completing placental transfusion in a shorter time than delayed cord clamping. The aim of this narrative review is to analyse the literature regarding umbilical cord milking in term and late-preterm infants and to assess all possible benefits and limits of this procedure in clinical practice, especially in comparison to immediate and delayed cord clamping. Methods . We analysed literature data concerning maternal, as well as neonatal, outcomes for term and late-preterm (gestational age ≥ 34 weeks) newborns who received umbilical cord milking. Results . Most studies show comparable benefits for both umbilical cord milking and delayed cord clamping, especially in terms of haematological parameters when compared to immediate cord clamping. Umbilical cord milking may be a feasible procedure also for newborns requiring resuscitation. Conclusions . Literature data concerning positive effects of umbilical cord milking are encouraging and suggest that umbilical cord milking may be a quick and effective method to provide placental transfusions to depressed infants. However, the lack of standardised procedures and the variation in evaluated outcomes as well as the limited number of patients enrolled in trials, along with the retrospective nature of some of them, prevent recommending umbilical cord milking as a routine procedure.